Marché de Ganvié - Adanhounsounou, Nounangnon Freeman (Brasil, 2023)
The African continent is divided into five regions, has 54 countries and unfortunately few are aware of its history, geography, culture, architecture and religion. Benin is a country in the west of the continent, where a special village called Ganvié is located. Architecture in Benin is an architecture that uses local, traditional materials. Also an architecture of stilts mainly in Ganvié Ganvié is a town on the shores of Lake Benin in the middle of Lake Nokoué, north of Cotonou. For travelers passing through West Africa, we suggest discovering this very harmonious lakeside village. In fact, Ganvié is a floating city with houses on stilts that has more than 40,000 inhabitants.